Oxidative stress parameters as biomarkers of risk factor for diabetic foot among the patients with type 2 diabetes - Oliveira,Ana Carla Pozzi (2014)
The aim of this study was to determine whether plasma levels of carbonylated proteins, total antioxidant capacity (TAC) and reduced protein thiols could be suitable biomarkers of risk factors for diabetic foot. Individuals with type 2 diabetes with normal protective sensation (normal foot group) vs. loss of protective sensation and/or signs of peripheral arterial disease and/or foot deformities and/or history of ulcers and/or neuropathic fractures and/or amputation (diabetic foot group) were compared. The diabetic foot group showed higher carbonylated protein levels (P = 0.0457) and lower levels of TAC (P = 0.0148) and reduced protein thiols (P = 0.0088), compared with the normal foot group. In general, several other parameters of risk of diabetes complication (blood levels of glycated hemoglobin, glucose and cholesterol, duration of diabetes, body mass index and waist circumference) showed a tendency of higher values in the diabetic foot group. The results suggest that the plasma levels of carbonylated proteins, TAC and reduced protein thiols could furnish information about the risk of diabetic foot, considering that the changes in these biomarkers were associated with the loss of sensitivity and foot ulcerations.